Chinese culture through legends and fiction : a guided reader - Zhang, Zhenjun, 1956- (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"This book provides a collection of selected and translated Chinese legends and tales arranged under specific topics important to Chinese culture, with an introduction and reading guide for each piece. Comprised of 4 parts covering Confucian culture, Daoist culture, Buddhist culture and topics beyond the Three Readings, the sources featured in this anthology include legends, fictional works, and historical texts, as well as philosophical texts of ancient China, ranging from the Han dynasty (206 BCE-220 CE) to the Qing dynasty (1644-1911). The book will help its readers learn about Chinese culture by immersing them in the wonderful world of traditional China, with the compelling tales selected for this collection revealing the fascinating meshwork of Chinese culture. Giving its readers a fascinating and effective way to learn about Chinese customs, traditions, and values by immersing themselves in Chinese culture via its legends and fiction this book will be an invaluable text for students and scholars of Chinese literature, culture and history, as well as general readers with an interest in China"--
Keywords: Chinese literature -- Translations into English; Legends -- China; Philosophy -- China; Literature and society -- China; China -- Literary collections; LITERARY CRITICISM / Asian / Chinese; LITERARY CRITICISM / Asian / General